PWE-003 Vasopressin contracts human isolated stomach muscle: possible role in nausea?. (28th May 2012) - Broad, J; Andrews, P L; Sanger, G J
Abstract : Introduction: Circulating levels of vasopressin are raised in association with nausea in humans and in species with an emetic reflex, whereas in rats exposed to emetic stimuli, levels of oxytocin but not vasopressin are raised. 1 One hypothesis is that vasopressin acts in the upper gut to help signal nausea, but in animals the concentrations which contract stomach muscle are usually higher than the concentrations measured in human plasma during nausea (around 10–200 pM). However, extreme species variations in gastric functions and genetics 2 means that studies must now be conducted with human stomach. Methods: Human stomach was obtained at surgery following informed consent. After removing the mucosa, strips were cut parallel to the circular muscle and suspended between ring electrodes in tissue baths for isometric recording (Kreb's; 5% CO2 in O2 ; 37°C; 2 g tension). Electrical field stimulation (EFS) was applied at 5 Hz (0.5 ms pulse width, 50 V, 10 s) every 1 min, for sub-maximal responses. N = number of patients. All drugs were added non-cumulatively. Results: In the gastric antrum, EFS-evoked contractions were prevented by 1 μM tetrodotoxin (n=3), attenuated by atropine 1 μM (n=3) and facilitated by the nitric oxide synthase inhibitor L-NAME 0.3 mM (by 11±7% n=14). Vasopressin (100 pM–100 nM) caused a concentration-dependent increase in baseline muscle tension of 230±68 mg, EC50 =1.2 nM, corresponding to a contraction equivalent to 226±118% of the EFS-evoked contraction (n=1–4 each concentration). However, there was no change in the magnitude of the contractions to EFS (+14±12% change at 100 nM). Elevated muscle tension persisted for >30 min in continued presence of the hormone (100 nM, n=4). In preliminary experiments with gastric fundus, only 100 nM vasopressin has been studied, being found to act similarly (an increase of 128 and 38 mg; n=2). Interestingly, oxytocin (100 nM) also increased baseline muscle tension in the antrum (by 164±64 mg, corresponding to an increase of 41±11% EFS; n=3), persisting for >30 min without affecting the magnitude of EFS evoked contractions (+13±4% change; n=3). Conclusion: Here we have shown for the first time that vasopressin and oxytocin have direct contractile effects on human isolated stomach muscle. The effective concentrations of vasopressin are within the range induced by nausea in humans. This indicates a potential direct role of vasopressin in signalling the induction of nausea in humans. Competing interests: None declared. References: 1. Stern RM, Koch KL, Andrews PL. Nausea: Mechanisms and Management . Oxford Univ Press, 2011. 2. Sanger GJ, Holbrook JD, Andrews PL. The translational value of rodent gastrointestinal functions: a cautionary tale. Trends Pharmacological Sci 2011;32 :402–9.